Rate of Serum Electrolyte Derangement among Pakistani Children Having Acute Diarrhea and Dehydration K.P.K North Population Base Study (Pakistan) - Khan, Muhammad Qasim; Ullah, Kiramat; Ahmad, Khalil; Rehman, Sijad Ur; Khan, Abbas Ali; Ullah, Inayat; Khan, Qasim; Din, Qiam Ud (American Journal of Health, Medicine and Nursing Practice, 2022)
Purpose: To study serum electrolyte derangements among children with acute diarrhea presenting with dehydration. Methodology: Cross-sectional and descriptive study in department of Pediatrics, MMC Hospital, Mardan (Pakistan) for from 01-02-2020 to 31-10-2020. A total of 390 children having acute diarrhea with dehydration were included. Five milliliters (5mls) of blood was drawn and estimation of serum Sodium and potassium levels were done. Findings: In 390 cases, 218 (55.9%) were males while 1 72 (44.1%) were females. The mean age was 2.5±1.5 years. Out of 390 cases, 2(0.51%) had no dehydration, some dehydration was noted in 218 (55.9%) cases while 170 (43.59%) cases had severe dehydration. Hypernatremia was noted in 218 (55.9%) cases and hypokalemia was noted in 77(19.74%) cases. Conclusion: High rate of hyponatremia and hypokalemia was seen in our study in children with acute diarrhea and dehydration. Hyponatremia and hypokalemia was significantly associated with age, gender and grades of dehydration.